Mojave [videorecording (DVD)] - Monahan, William; Isaac, Oscar; Wahlberg, Mark, 1971-; Hedlund, Garrett, 1985- (A24 / Lions Gate Entertainment, 2016)
A brilliant suicidal artist, Thomas, attempts to escape his privileged existence by heading out to the desert, only to encounter homicidal, chameleon-like drifter Jack. Their first encounter at a campfire sets up a nonstop, violent duel of physical and intellectual equals, a chase that moves from the spectacular vistas of the American desert to a noir Los Angeles, where Thomas's notoriety as an artist is revealed.